Diseño y simulación de torre de enfriamiento por evaporación. (2020)
The present work is focused on the design and simulation of an evaporative cooling tower with the educational purpose of being a Transfer Laboratory team. This design is calculated and verified by means of the CFD mechanical design software using the mathematical models offered by the program, which simulate heat transfer processes and temperature changes produced by cooling. Initially, the operating parameters and amed specifications are defined for later design and simulation. The lines of this work are framed in the Energy area, which includes subjects such as Heat Transfer and Thermodynamics and Fluid Mechanics. The students of the University Antonio Nariño campus Tunja will be the beneficiaries with the use of the design of the evaporative cooling tower, as a theoretical base, which can be compared with experimental data, if one wanted to carry out its implementation or its construction. For the development of the project, institutional resources and own resources are available as design tools and their licenses. At the end of the project, it is expected to have a design with simulation and results for later use as a basis for comparison.